The Clinical and Pathological Landscape of Pediatric Appendicitis in Central Java, Indonesia: A Retrospective Cohort Study Highlighting a High Burden of Delayed Diagnosis - Dimas Susilo Waridiarto; Edwin Basyar; Rudiyuwono Raharjo (HM Publisher, 2025)
Background: The timely diagnosis of pediatric appendicitis is a global challenge, particularly in low- and middle-income countries where health system barriers can lead to significant delays and increased morbidity. This study aimed to characterize the clinical and pathological presentation patterns of pediatric appendicitis at a major Indonesian referral center to identify evidence of diagnostic delay and to analyze associated surgical management trends. Methods: A retrospective cohort study was conducted at Dr. Kariadi General Hospital on all pediatric patients (n=52) who underwent appendectomy between January 2022 and December 2024. Data on demographics, definitive histopathological diagnoses, and surgical approaches were collected and analyzed. The manuscript was prepared in accordance with the STROBE guidelines for observational studies. Results: The cohort was predominantly male (63.4%), with a peak incidence in the 6–10 year age group (42.3%). The most striking finding was the histopathological diagnosis: a remarkable 48.0% of patients were diagnosed with chronic appendicitis with acute exacerbation, a strong indicator of delayed presentation. Minimally invasive surgery was performed in 48.0% of cases. While a significant association was observed between laparoscopic surgery and a shorter postoperative length of stay (p < 0.001), this finding was subject to significant confounding by indication. Conclusion: The exceptionally high prevalence of chronic exacerbated appendicitis is the principal finding of this study, serving as a powerful public health signal for systemic delays in the pediatric acute care pathway in this region. While minimally invasive surgery is associated with faster recovery, the more pressing priority is addressing the upstream factors—including public awareness and primary care referral systems—that lead to late surgical presentation and increased cumulative morbidity.